2012
DOI: 10.1002/imhj.21372
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal Representations of Family in Parents and Coparental Interactions as Predictors of Triadic Interactions During Infancy

Abstract: In this study, we explored the predictive role of family interactions and family representations in mothers and fathers during pregnancy for postnatal mother-father-infant interactions during the first 2 years after birth. Families (N = 42) were seen at the fifth month of pregnancy and at 3 and 18 months after birth. During pregnancy, parents were asked to play with their baby at the first meeting by using a doll in accordance with the procedure of the prenatal Lausanne Trilogue Play (LTP;Corboz-Warnery, 2010)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
1
3

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 51 publications
(39 citation statements)
references
References 52 publications
1
34
1
3
Order By: Relevance
“…Although prior research has linked prenatal perceptions and representations of coparenting to postpartum coparenting behavior (McHale et al, 2004; McHale & Rotman, 2007), and has connected prenatal coparenting behavior to postnatal family alliance (Carneiro et al, 2006; Favez et al, 2013), this is the first study documenting continuity between prenatal and postnatal coparenting behaviors. Even after controlling for both observed couple behavior and reported relationship functioning, partners who engaged in higher quality prenatal coparenting behavior in the PLTP showed greater supportive coparenting and less undermining coparenting behavior at 9 months postpartum.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…Although prior research has linked prenatal perceptions and representations of coparenting to postpartum coparenting behavior (McHale et al, 2004; McHale & Rotman, 2007), and has connected prenatal coparenting behavior to postnatal family alliance (Carneiro et al, 2006; Favez et al, 2013), this is the first study documenting continuity between prenatal and postnatal coparenting behaviors. Even after controlling for both observed couple behavior and reported relationship functioning, partners who engaged in higher quality prenatal coparenting behavior in the PLTP showed greater supportive coparenting and less undermining coparenting behavior at 9 months postpartum.…”
Section: Discussionmentioning
confidence: 91%
“…Instead, because the PLTP was adapted from the original, postnatal Lausanne Trilogue Play procedure (Fivaz-Depeursinge & Corboz-Warnery, 1999), which was designed to assess family alliance via mother-father-infant triadic interactions, research using the PLTP has focused on its ability to predict subsequent family alliance (Carneiro et al, 2006; Favez et al, 2012; Favez, Frascarolo, Lavanchy Scaiola, & Corboz-Warnery, 2013). However, family alliance quality is not synonymous with coparenting behavior.…”
Section: History Of the Prenatal Lausanne Trilogue Play (Pltp)mentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, thanks to its prenatal version (Prenatal LTP; Carneiro et al, 2006), it permits the examination of the co-parental interactive behaviors during pregnancy, in accordance with the definition of co-parenting as the quality of the coordination presented by the interactive exchanges between two parents while they are taking care of their child (Minuchin, 1974; McHale, 1995). Continuity has been attested between expectant parents’ exchanges and postnatal co-parental interactive features, and prenatal interactions are recognized as one of the most important predictors of later family interactions’ quality (Carneiro et al, 2006; Simonelli et al, 2012; Favez et al, 2013). Thus, co-parental abilities during pregnancy can be conceived as an interactive matrix for the construction of early family relationships.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…On one side, studies (Favez et al, 2006a, 2013) reported the absence of a link between marital satisfaction and the quality of family interactions. On another side, an association has been detected between marital satisfaction in the prenatal period and the evolution of family interactions over the first 18 months of child’s life (Favez et al, 2006b; Darwiche et al, 2015), with high marital satisfaction predicting a decreasing pattern of family interactions.…”
Section: Theoretical Backgroundmentioning
confidence: 99%